Analisis Kegunaan Website Penerimaan Mahasiswa Baru Menggunakan Metode System Usability Scale - Adnan, Andhika (Universitas Boyolali, 2025)
Advances in information technology have prompted universities to utilise digital systems in administrative processes, including the admission of new students (PMB). Universitas Widya Dharma Pontianak has developed a PMB website as an online registration tool, but no systematic evaluation of its usability has been conducted. This study aims to analyse the usability of the PMB website using the System Usability Scale (SUS) method. The study employs a quantitative approach, distributing SUS questionnaires to 294 respondents selected via simple random sampling from a total population of 1,102 prospective new students for the 2025/2026 academic year. Data were analysed by calculating each respondent's SUS score, then determining the overall average score and its interpretation based on SUS standards. The results showed that the PMB website achieved an average score of 93, which falls into the “A” grade category, an “acceptable” acceptance level, and an “excellent” adjective rating. These findings indicate that the PMB website has a very high level of usability, is easy to use, and provides high satisfaction for users. However, the study also recommends further development regarding improved accessibility and interactive features to support a broader user experience.